Temperature effects on fine-grained soil erodibility - Al-Ali, Abdullah Mubarak Abdulmohsen (Kansas State University, 2016)
Recent climate changes may affect the stability of our infrastructure in many ways. This study investigated the effects of fine-grained soil temperature on erosion rate. If climate change is shown to affect the erodibility of soils the impacts must be identified to monitor the stability of existing infrastructure, improve design of levees and structures founded in erosive environments, and to prevent sediment loss and stream meanders. Fine-grained soil erosion is complicated by the dynamic linkage of multiple parameters, including physical, biological and geochemical properties. This study held constant all parameters that influence fine-grained soil erodibility while only varying soil temperature in order to study the effects it has on erodibility. This study also confirmed previous findings that water temperature affects soil erodibility. The main objective of this study was to investigate the effects of fine-grained soil temperature on erosion rate. This study also instrumented a turbidity sensor to reliably map soil erosion. Based on this research, the conclusion was made that an increase in soil temperature increases soil erosion rate. The turbidity sensor was a valuable tool for comparing soil erosion. Future studies should investigate the effects soil temperatures below room temperature, the magnitude of temperature increase or decrease, and the effects of cyclic heating and cooling on fine grained soil erodibility.
Keywords: Erosion; Fine-grained soil; Temperature Effects; Erosion Function Apparatus; EFA